Pengaruh latihan gerak aktif terhadap intensitas nyeri rematik pada lansia - ., Adi Antoni; ., Nurhabibah Lubis (Jurnal Kesehatan Ilmiah Aufa Royhan, 2018)
Rheumatoid arthritis is a degenerative problem that often occurs in the elderly. One symptom that is often caused by rheumatoid arthritis is joint pain. One of the actions of nursing in overcoming musculoskeletal disorders is an active range of exercise. The purpose of this study was to find out the effect of exercise on the range of active motion on the intensity of rheumatic pain in the elderly. The research design used was quasi-experimental with the design of One group pre-test and post-test only design. The sampling technique used Purposive Sampling with 16 subjects as the research subjects. This study used the Wilcoxon Test analysis. The results showed the influence of the active range of motion exercises on rheumatic pain intensity in the elderly with a mean pre-test value of 4.88 (SD:0.953) and a mean posttest 3.88 (SD: 1.143) p-value = <0.0001. The results of this study can be one alternative in dealing with rheumatic pain in the elderly without the need for the cost and side effects.